Evaluation of a novel SARS‐CoV‐2 rapid antigenic test diagnostic value in respiratory samples; is the reported test accuracy similar to values in the real‐world? A cross‐sectional study. Issue 5 (10th August 2022) - Hatami, Hossein; Rezaeian, AhmadReza
Abstract: Background and Aims: Although reverse transcription‐polymerase chain reaction (RT‐PCR) assay was introduced as the gold standard to detect SARS‐CoV‐2, the method was known to be time‐consuming besides the requirement for an equipped laboratory. This survey aims to investigate a novel SARS‐CoV‐2 antigen test as a diagnostic tool in COVID‐19 patients to overcome these limitations in addition to evaluating COVID‐19 population characteristics. Methods: A retrospective cross‐sectional study was carried out during the first semester of 2021, and about 1070 nasopharyngeal samples were collected to compare the E‐Health Barakat Company SARS‐CoV‐2 antigen rapid test results with RT‐PCR reports as the reference method. Results: Totally 537 participants were included in this study for employing RT‐PCR and the antigen test sequentially. The novel antigen rapid test sensitivity is considered 21.09% in the real world, though 81% in the manufacturer's instruction has been mentioned. Moreover, the most revealed manifestations were found respiratory symptoms and fatigue sensations. Conclusion: This study is the first one on evaluating the SARS‐CoV‐2 antigen test in our country. Although the novel antigen assay was found quick and easy to perform, the test performance was very disappointing. The extensive false‐negative results made it an inappropriate candidate for mass screening.